Experimental study on the operating characteristics of refrigerant pumps for solar ejector refrigeration systems. (June 2022) - Tian, Guoji; Zhao, Chengming; Zheng, Huifan; Fan, Xiaowei
Highlights: The application feasibility of centrifugal pump in ejector refrigerant system is proved. Operating characteristics of refrigerant pumps were experimentally studied. The optimal working range of pump efficiency under variable working conditions is obtained. Abstract: A bench performance test for a refrigerant pump was built to analyze the variations among parameters such as flow rate, head, rotational speed, efficiency/total efficiency and power consumption of a multistage centrifugal pump under different working conditions. The study showed that the outlet pressure, differential pressure and power consumption of the pump increased with increasing frequencies at the rated flow rate of 1 m 3 /h and inlet pressure p c = 0.454 MPa. The total pump efficiency showed a trend toward first increasing and then decreasing, and the maximum value was approximately 27.7%. When the refrigerant pump was at a frequency of 37.5 Hz and the inlet pressure was between 0.338 and 0.523 MPa, the pump outlet pressure and differential pressure decreased with increasing flow rates, and the pump outlet pressure increased with increasing inlet pressures. While the pump differential pressure increased with the increase in suction pressure, the pump power consumption increased with the increase in flow and increased slowly with the pump inlet pressure. With the increase in the flow rate, the total efficiency of the pump showed a tendency toward first increasing and then slowly declining. The total efficiency of the pump was between 4.0% and 30.2% at flow rates between 0 and 1.8 m 3 /h. Under the same conditions, when the pump operated under low flow rate and high pressure differential conditions, and the refrigerant pump efficiency was low.